Endodontic Management of Three-rooted Mandibular First Premolar Using Cone-beam Computed Tomography: A Case Report - Mahdavisefat, Elham; Kazemi, Ali; Moghtaderi Esfahani, Ehsan (Iranian Endodontic Journal, 2023)
The anatomy of the root canal system always affects endodontic treatment outcomes. Mandibular premolar teeth demonstrate extreme variations in root canal morphology. Mandibular first premolars typically exhibit basic single-root and single-canal anatomy. The occurrence of three roots in the mandibular first premolar has not been commonly reported in the literature. This article reported a case of a 26-year-old male with spontaneous pain of the mandibular first premolar representing the presence of an extra canal on the periapical radiograph. Cone-beam computed tomography (CBCT) was used to assess the root canal details which led to the finding of three canals. Further, a periapical bone defect was detected, and finally, the nonsurgical endodontic management of the mandibular first premolar with three canals and three different apical foramina was performed in one session.